miR-1323 Promotes Cell Migration in Lung Adenocarcinoma by Targeting Cbl-b and Is an Early Prognostic Biomarker - Zhao, Huan; Zheng, Chunlei; Wang, Yizhe; Hou, Kezuo; Yang, Xianghong; Cheng, Yang; Che, Xiaofang; Xie, Shilin; Wang, Shuo; Zhang, Tieqiong; Kang, Jian; Liu, Yunpeng; et al. (Frontiers in Oncology, 2020)
Purpose: MicroRNAs are known to regulate cellular processes in non-small cell lung cancer (NSCLC) cells and predict prognosis. However, identification of specific microRNAs in NSCLC as potential therapeutic targets is controversial. We aim to determine the clinical significance of miR-1323 in the prognosis of patients with lung cancer and the potential mechanism. Patients and methods: A bioinformatics approach was used to screen the importance microRNA in NSCLC through the online GEO database (GSE42425). The relationship between expression level of miR-1323 and overall survival of lung cancer patients was analyzed. Additionally, an independent corhort including 54 NSCLC cases that underwent resection validated the connection between miR-1323 and LUAD patients’ overall survival. Next, the function of miR-1323 was studied in vitro by transient transfection. A more in-depth mechanism was studied through luciferase reporter gene experiments. Results: High miR-1323 expression correlated with poor survival in NSCLC patients (P=0.011), and in lung adenocarcinoma (LUAD) patients (P=0.015) based on GEO database (GSE42425). In the independent cohort based on our hospital, high miR-1323 expression was associated with LUAD patients (P=0.025). Moreover, transfection with mimics of miR-1323 showed an increased migratory capacity in LUAD A549 and HCC827 cells. In addition, E3 ubiquitin-protein ligase Casitas B-lineage Lymphoma-b (Cbl-b) was found to be the target genes of miR-1323 and significantly down regulated after mimics of miR-1323 transfection, and high Cbl-b expression predicted better prognosis in NSCLC and LUAD (P=0.00072 and P=0.02, respectively). Conclusion: The miR-1323 promoted LUAD migration through inhibiting Cbl-b expression. High miR-1323 expression predicted poor prognosis in LUAD patients.